Ocean acidification induces distinct metabolic responses in subtropical zooplankton under oligotrophic conditions and after simulated upwelling - Osma, N; Vargas, CA; Alguero-Muniz, M; Lennart Bach; Gomez, M; Horn, HG; Ludwig, A; Packard, TT; Riebesell, U; Romero-Kutzner, V; Taucher, J; Fernandez-Urruzola, I (2022)
Ocean acidification (OA) is one of the most critical anthropogenic threats to marine ecosystems. While significant ecological responses of plankton communities to OA have been revealed mainly by small-scale laboratory approaches, the interactive effect of OA-related changes on zooplankton metabolism and their biogeochemical implications in the natural environment still remains less well understood. Here, we explore the responses of zooplankton respiration and ammonium excretion, two key processes in the nutrient cycling, to high p CO 2 levels in a 9-week in situ mesocosm experiment conducted during the autumn oligotrophic season in the subtropical northeast Atlantic. By simulating an upwelling event halfway through the study, we further evaluated the combined effects of OA and nutrient availability on the physiology of micro-and mesozooplankton. OA conditions generally resulted in a reduction in the biomass-specific metabolic and enzymatic rates, particularly in the mesozooplankton community. The situation reversed after the nutrient-rich deep-water addition, which initially promoted a diatom bloom and increased heterotrophic activities in all mesocosms. Under high p CO 2 conditions (>800 μatm), however, the nutrient fertilization triggered the proliferation of the harmful alga Vicicitus globosus , with important consequences for the metabolic performance of the two zooplankton size classes. Here, the zooplankton contribution to the remineralization of organic matter and nitrogen regeneration dropped by 30% and 24%, respectively, during the oligotrophic period, and by 40% and 70% during simulated upwelling. Overall, our results indicate a potential reduction in the biogeochemical role of zooplankton under future ocean conditions, with more evident effects on the large mesozooplankton and during high productivity events.